2018
DOI: 10.3390/ijms19051465
|View full text |Cite
|
Sign up to set email alerts
|

Function of the ERFL1a Transcription Factor in Wheat Responses to Water Deficiency

Abstract: The APETALA2/ethylene response factor (AP2/ERF) superfamily is involved in the responses of plants to biotic and abiotic stresses; however, the functions and mechanisms of some members of this family in plants are unclear. In our previous study, expression of TaERFL1a, a member of the AP2/ERF family, was remarkably induced in wheat seedlings suffering freezing stress. In this study, we show that its expression was rapidly upregulated in response to salt, cold, and water deficiency, suggesting roles in the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…For instance, DREBs (including TINY, CBF1, ERF53, RAP2.4, and TG/RAP2.4A) and ERFs (including ERF1, ERF4, and ERF71) bind to both DRE and ERE elements (Lin et al, 2008; Sun et al, 2008; Yang et al, 2009; Cheng et al, 2012; Zhu et al, 2014; Lee et al, 2015). Similarly, the conserved DNA binding preferences of AP2/ERF are also expanded to other species such as rice (Wan et al, 2011), wheat (Gao et al, 2018), maize (Liu et al, 2013), soybean ( Glycine max ) (Zhang et al, 2009), and tobacco ( Nicotiana tabacum ) (Park et al, 2001). Recently, the combination of high-throughput protein-binding microarray and relevant transcriptome data demonstrated that transcription factors with high structure identity share similar DNA binding sites, which also enables them to share some biological relevance and explains their functional redundancy (Franco-Zorrilla et al, 2014).…”
Section: Overview Of Ap2/erf Family Transcription Factorsmentioning
confidence: 99%
“…For instance, DREBs (including TINY, CBF1, ERF53, RAP2.4, and TG/RAP2.4A) and ERFs (including ERF1, ERF4, and ERF71) bind to both DRE and ERE elements (Lin et al, 2008; Sun et al, 2008; Yang et al, 2009; Cheng et al, 2012; Zhu et al, 2014; Lee et al, 2015). Similarly, the conserved DNA binding preferences of AP2/ERF are also expanded to other species such as rice (Wan et al, 2011), wheat (Gao et al, 2018), maize (Liu et al, 2013), soybean ( Glycine max ) (Zhang et al, 2009), and tobacco ( Nicotiana tabacum ) (Park et al, 2001). Recently, the combination of high-throughput protein-binding microarray and relevant transcriptome data demonstrated that transcription factors with high structure identity share similar DNA binding sites, which also enables them to share some biological relevance and explains their functional redundancy (Franco-Zorrilla et al, 2014).…”
Section: Overview Of Ap2/erf Family Transcription Factorsmentioning
confidence: 99%
“…In bread wheat, however, the multiple copy insertions, low transformation efficiency, cultivar specificity, time consumption, and high cost of transgenic approaches have greatly limited gene function studies in this species [23]. The functional redundancy among homoeologs in this species also causes some difficulties in terms of generating null mutants [24]. BSMV-VIGS method facilitates the rapid generation of gene knockdown phenotypes in polyploid species because plant transformation is not required, accelerating the characterization of target genes [25].…”
Section: Resultsmentioning
confidence: 99%
“…BSMV‐GFP was used as negative control 33 . Vector construction and virus inoculation were performed according to our previous study 34 . Phenotypes of inoculated wheat plants were observed, and transcript levels of TaHAK1 gene were measured at 8 days after virus inoculation.…”
Section: Methodsmentioning
confidence: 99%